Right Testicular Vein Draining into Right Renal Vein: A Case Report - Santanu Kumar Sarma; Alakesh Gogoi; Jayasri Devi (Journal of Clinical and Diagnostic Research)
During routine dissection of an adult male cadaver about 50 years of age, the right testicular vein was seen to drain into the right renal vein at a right angle which is rare. At a 90° angle, the left testicular vein drain into the left renal vein. The caudal part of subcardinal vein is responsible for the development of gonadal vein and it drains into the supra-subcardinal anastomosis. In this exceptional case, the right supra-subcardinal anastomosis instead contributed to the formation of the right renal vein, which consequently received the right testicular vein. On the left side, the supra-subcardinal anastomosis is incorporated into the left renal vein, serving as the drainage site for the left gonadal vein. This pattern of drainage has to be kept in mind by the physicians as this may lead to varicocele on the right which may be implicated in male infertility.